(untitled) (Stato, Chiese e pluralismo confessionale, 2020)
SOMMARIO: 1. Premessa - 2. Spazio giuridico europeo e rilevanza penale della condotta - 3. Appartenenza cultural-religiosa e consapevolezza dell’agire - 4. Cultural defense e opzioni di diritto penale laico: il caso delle MGF come reato di genere - 5. Il terrorismo di ispirazione religiosa: un approccio multisettoriale per la lotta al fenomeno - 6. Brevi notazioni conclusive: mediazione interculturale e metodi di trasformative accomodation. New Frontiers of Culturally Motivated Crimes. The Intercultural Method-Approach as a Tool to Prevent and Counter Religion-Inspired Crimes ABSTRACT: This paper analyses the so-called culturally motivated crimes, focusing the attention on legal measures that may prevent and counter such misconducts. The Author points out some methods, such as those referring to the transformative accommodation, which may be able to solve conflicts between the need to safeguard human rights, including those related to religious freedom, and the Government’s priority to protect public safety. From here stems the investigation on the so-called Islamic terrorism that, under some aspects, can be seen as a new frontier of religion-inspired crimes. This, on the other hand, suggests a multisectoral approach, which is important in order to deal with very serious threats while promoting intercultural and inter-religious integration.